Private Financial Institutions and their Role in the Development of Small and Medium sized Enterprises in Iraq - بريهي, فارس كريم; نعيم, حسين شريف (Journal of Economics and Administrative Sciences, 2016)
the reality of small and medium enterprises analysis reflects weaknesses plaguing these enterprises and strengths that are characterized by, and thus the formulation of appropriate solutions to the obstacles faced by these enterprises to enhance its contribution to the achievement of economic and social development. Iraqi small and medium enterprises suffer from several obstacles stand in front of development and  support their competitiveness, the finance one of the main obstacles which impede growth and development of these enterprises, noting the banking system in Iraq reluctance to lend to small and medium-sized enterprises, as a result of the high cost of lending these enterprises compared to large projects, as well as the inability of these enterprises provide sufficient guarantees required by banks, in addition to lack of information on these enterprises, prompting banks consider this risky high projects, and this is why necessarily to adopt mechanisms and programs that will reduce the obstacles facing the financing of these enterprises and holds the linkage task between enterprises on the one hand The banks on the other hand, and thus contributing to improve the chances of these enterprises is to obtain appropriate financing. Through this need arose after the year 2003 private financing institutions that focus on supporting small and medium enterprises to exceed the limitations and obstacles imposed by the banking funders that. Where the CBI initiated in cooperation with the US Agency for International Development, introduced the idea of ​​small and medium-Iraqi private banks enterprise finance, has crystallized the idea Created two companies (the Iraqi Company for Bank Guarantees, the Iraqi Company for Financing SMEs).